TLE1 Positive Clear Cell Sarcoma of the Kidney: A Case Report and Review of the Literature - Rana Naous (Case Reports in Pathology)
Clear cell sarcoma of the kidney (CCSK) is an uncommon malignant tumor of uncertain histogenesis that occurs most commonly in childhood. Histologically, CCSK can mimic myxoid variant of synovial sarcoma (SS); however, the double positivity for CD99 and TLE1 in SS helps in excluding CCSK. Herein, we report a rare case of CCSK arising in the left kidney of a 3-year-old girl. The mass grossly measured 9.5 cm in maximum dimension and histologically showed the classic arborizing fibrovascular septae and background myxoid matrix that is usually seen in CCSK. The tumor however was double positive for CD99 and TLE1 which made it difficult to discriminate it from the myxoid variant of SS based on histopathological examination and immunophenotype alone, and genetic analysis for SYT gene rearrangement was required to reach a definitive diagnosis. Although there have been previous case reports of CCSK with positive expression of CD99 and negative TLE1, to our knowledge, this is the first case of CCSK expressing both CD99 and TLE1.